2008
DOI: 10.1021/ja802991y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Study of the Mechanism and Enantioselectivity of Palladium- Catalyzed Intermolecular Heck Coupling

Abstract: The asymmetric Heck reaction using P,N-ligands has been studied by a combination of theoretical and experimental methods. The reaction follows Halpern-style selectivity; that is, the major isomer is produced from the least favored form of the pre-insertion intermediate. The initially formed Ph-Pd(P,N) species prefers a geometry with the phenyl trans to N. However, the alternative form, with Ph trans to P, is much less stable but much more reactive. In the preferred transition state, the phenyl moiety is trans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 30 publications
(21 reference statements)
3
46
0
Order By: Relevance
“…[8, 9k] A recent quantum-chemical study even showed that, in one example, the migratory insertion of 1 occurs from the least-favored intermediate. [29] The consistently high ee values obtained with iPr 2 NEt as base corroborate, at least, that BINAP(O) acts as a bidentate ligand, and the minor deviations in the ee values of 2 and 3 (both R configuration) do not support a kinetic-resolution pathway.…”
Section: Resultsmentioning
confidence: 72%
“…[8, 9k] A recent quantum-chemical study even showed that, in one example, the migratory insertion of 1 occurs from the least-favored intermediate. [29] The consistently high ee values obtained with iPr 2 NEt as base corroborate, at least, that BINAP(O) acts as a bidentate ligand, and the minor deviations in the ee values of 2 and 3 (both R configuration) do not support a kinetic-resolution pathway.…”
Section: Resultsmentioning
confidence: 72%
“…24 Computational studies of the effects of halides or acetates have been published by Shaik 25 and by Norrby. 26 Some very interesting results showing high activity of palladium in the presence of acetate anions were published by Reetz 27 and by de Vries. 28 In view of these reports, we decided to run the same experiments in the absence of any ligand, as it is plausible that the active palladium species does not contain the ligand.…”
Section: Application In Catalysismentioning
confidence: 95%
“…224 This means that the major isomer is formed from one of the higher energy pre-insertion intermediates (Scheme 10). While the trans Ph−N arrangement is more favorable over the trans Ph−P arrangement, the higher barrier of the subsequent furan insertion and the lower stability of the formed carbopalladated species make the trans Ph−N pathway less productive.…”
Section: Stille Couplingmentioning
confidence: 99%